Experimental Study on the Mechanical Property of Loess Mixed with Bentonite-HDTMA - Zhang Ming; Chen Guozhou; Liu Yang; Huang Shouhai (Advances in Materials Science and Engineering)
Malan loess in the middle and lower reaches of the Yellow River after mixed with different bentonite and HDTMA ratios was selected to carry out shear and consolidation tests for discussing the influence of bentonite-HDTMA on the mechanical property of loess lining material in landfills. Studies have shown that, after mixing 6% to 14% bentonite, the cohesive force of modified loess is significantly increased, the friction angle is reduced and remains stable, and the shear strength is improved. The compressibility of materials slightly decreases with the increase of bentonite ratio. The addition of 2%–4% HDTMA weakens the increment for the cohesive force caused by bentonite, but the friction angle is effectively recovered. The compressibility of materials increases with the increase of HDTMA ratio. As the dry density increases, the shear strength of the modified loess increases, and the compressibility coefficient decreases. The mechanical property of loess lining material can be optimized by adding 6%–14% bentonite. The incorporation of 2%–4% HDTMA does not have a significant negative impact on the optimization effect of bentonite. From the perspective of the mechanical property, it is recommended that the dry density of modified loess is 1.70 g/cm3, the bentonite ratio is 10%–14%, and the HDTMA ratio is 2%–4%.